Introduction to bio-based materials and biotechnologies for eco-efficient construction - Pacheco-Torgal, F. (2020)
This chapter introduces some sustainability challenges, as well as the importance of resource efficiency and the European bioeconomy strategy. The importance of biobased materials and biotech admixtures for eco-efficient construction is summarized. The importance of changing the curriculum of civil engineering to address sustainability challenges and also enhance the collaboration between civil engineers and biotech experts is briefly discussed. Comments concerning the biobased and biotech related publication intensity of several well know civil engineering departments are also made. An outline of the book is also given.